The influence of new information and communication technologies in the teaching-learning process of the english language, to develop the productive skills, in the students of 7th year of basic education at Unidad Educativa Integral del Pacifico, during the school year 2013-2014. - Zambrano Batallas, Rubén Darío (2014)
This thesis project focuses on the use of the Information and Communication Technologies, the impact these have on the educational field, specifically in the study of English as a second language. In addition to its utility in the development of productive English language skills. The research was conducted in UNIDAD EDUCATIVA PARTICULAR DEL PACÍFICO in students of seventh year. The main objective was to establish the performance of English classes developed through technological resources, its impact, interest, and implementing them to help develop productive skills in students. To achieve the collection of information of the questions, a survey was developed to students in the seventh year, interview teachers responsible for such courses and observation sheet applied in their classes. The information obtained was submitted to statistical tables which actually reflected the technologies were not an essential part in English classes, thus being a limitation upon teach the classes, the activities were mostly in traditional way, and therefore it fails to obtain significant results in the development of student skills. Using technology today has become a fundamental part of the teaching-learning process of the English language, being so important that teachers plan their classes including technological resources which help not only to catch the attention of their students but also to develop their skills. It is for this reason that the proposal presented in the thesis project is based on the development of activities on websites and software that allow both the teacher and the student achieve their objectives and significantly increase the knowledge of the language